(untitled) (Baghdad Science Journal, 2025)
The predisposing factors and their effect on the increasing of vulvovaginal Candidiasis have been studied in this research. The result indicated that the highest of infection with vaginal Candidias was in the age of women with age of (21-30years) with vaginal itching and discharge, also the results revealed that the pregnancy was the main predisposing factor. The percentage of the infected pregnant Ladies was 33.7% followed by the women who used the IUCD and OCP 22.1%, those who used steroids 5.2% comparing with control women (without predisposing factors).The results also indicated that the most cases of infection were during the third trimester of pregnancy (where the rate of infedion) was 53.9%.-OCP- Oral Contraceptive Pills-IUCD- Intrra Uterine Contraceptive Device